Pornography and Sexual Deviance : A Report of the Legal and Behavioral Institute, Beverly Hills, California. - Goldstein, Michael J. (UC Press voices revived., 2022)
Does pornography represent ""a clear and present danger' to our society? This issue is being debated in the courts with increasing frequency, and is intimately tied to the broader issue of censorship and the voiding of first amendment protection which it implies. This volume deals both with the psychological effects of exposure to erotica and with the legal implications of censorship of pornography. This title is part of UC Press's Voices Revived program, whic.